The Impact Cost Factor Production on the Sheep Farmer’s Household Economics - Muhammad Ardi Wiranata (Medikun Publisher, 2024)
Sheep is a promising business opportunity, aside from being a commodity of export sheep in several ASEAN countries, to date Indonesia has not been able to provide export opportunities for sheep or goats, including contributors to sheep and goats as well as gradually also as farmers. The existence of livestock is a daily capital or savings that can support the lives of farmers, requires the time needed to manage livestock that can be used in addition to farmers. This study aims to calculate all the components of costs, income, earnings obtained as well as factors that increase sheep farming in East Java. This study analyzes the use of business analysis R/c ratio, and multiple linear regression to understand the factors that influence production. The results of the analysis show a loss figure of Rp. 226,752,000. Seven factors that significantly affect the income of household sheep farmers education, experience, land occupied, status of livestock, feed costs, other costs, and VOVD costs have a positive contribution to the income of farmers